2018
DOI: 10.22631/ijaep.v7i1.218
|View full text |Cite
|
Sign up to set email alerts
|

Effects of 8-Week Thera-Band Training on Spike Speed, Jump Height and Speed of Upper Limb Performance of Young Female Volleyball Players

Abstract: Introduction and objectives: Elastic resistance has been commonly used in the therapeutic and fitness setting. However, the effects of a strength training program using elastic resistance exercises to the explosive power and spike speed, which are very important elements for successful volleyball practice, has not been clearly demonstrated. Therefore, the aim of this study was to establish the effects of 8-week Thera-Band training protocols on the development of spike speed, counter movement jump (CMJ) height,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 49 publications
1
17
0
2
Order By: Relevance
“…This result is supported by the result of previous research revealing that a training program based on resistance could enhance the average speed of tennis serve for adolescent [22]. Another study conducted by [23] added that the combination of resistance band training was effective to increase the jump height, arm strength, speed and agility. Basically, strength training uses the principle of progressive overload, forcing the body (muscles, tendons, bones, etc.)…”
Section: Discussionsupporting
confidence: 71%
“…This result is supported by the result of previous research revealing that a training program based on resistance could enhance the average speed of tennis serve for adolescent [22]. Another study conducted by [23] added that the combination of resistance band training was effective to increase the jump height, arm strength, speed and agility. Basically, strength training uses the principle of progressive overload, forcing the body (muscles, tendons, bones, etc.)…”
Section: Discussionsupporting
confidence: 71%
“…Kumar et al [5] revealed that the characteristic of volleyball is that it requires the players to jump. Agopyan et al [6] in a study also suggested that volleyball players have a high vertical jump. This means that each player must have strong power to jump as provisions for hitting, blocking, and serving.…”
Section: Introductionmentioning
confidence: 91%
“…Athletes are more likely to participate in traditional resistance exercise regimens in order to improve their muscle strength. These workouts are carried out with sporting equipment such as dumbbells or gadgets, elastic bands, or the body's own weight [4]. Ballistic Six training program, which comprises regularly utilized upper body movements, was previously advised for overhead-throwing sportsmen [5].…”
Section: Introductionmentioning
confidence: 99%